2022
DOI: 10.1111/ijcs.12883
|View full text |Cite
|
Sign up to set email alerts
|

Marketing education to international students: A systematic literature review and future research agenda

Abstract: Even though numerous studies provide information on marketing education to international students, research that reviews the accrued knowledge holistically remains elusive.Accordingly, the main purpose of this study is to (1) systematically synthesize, compile and understand the existing line of empirical research on the topic of marketing education to international students and (2) outline a comprehensive future research agenda to help further advance this field. This study adopts the theory-context-character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 114 publications
0
9
0
Order By: Relevance
“…Finally, while it represents a start, our work is obviously not the last word on this important topic, and we recommend future studies to include more technologies and more nuanced affective and cognitive beliefs and analyse how it is challenged or empowered by the role of the sales assistant in phygital retail. At the same time, as pointed out by Paul et al (2023) discussing about Chat GPT, despite the great potential technologies have in enhancing consumer engagement and improving marketing practices, future research should consider the potential concerns about ethical considerations, consumer privacy and security.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, while it represents a start, our work is obviously not the last word on this important topic, and we recommend future studies to include more technologies and more nuanced affective and cognitive beliefs and analyse how it is challenged or empowered by the role of the sales assistant in phygital retail. At the same time, as pointed out by Paul et al (2023) discussing about Chat GPT, despite the great potential technologies have in enhancing consumer engagement and improving marketing practices, future research should consider the potential concerns about ethical considerations, consumer privacy and security.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, another aspect of understanding prosumers' sharing economy engagement in the digital era has been gaining in importance. With artificial intelligence (AI) chatbots (e.g., ChatGPT) and similar AI‐based tools now widely accessible, consumers, providers, and sharing economy platforms can gain access to efficient information and effective means of P2P communication (Paul et al, 2023). While researchers have only begun to discuss the changing landscape of marketing and consumer behavioral research in this era (e.g., Mehta et al, 2022; Paul et al, 2023), the use of AI chatbots likely will transform how consumers, providers, and platforms make decisions.…”
Section: Discussionmentioning
confidence: 99%
“…With artificial intelligence (AI) chatbots (e.g., ChatGPT) and similar AI‐based tools now widely accessible, consumers, providers, and sharing economy platforms can gain access to efficient information and effective means of P2P communication (Paul et al, 2023). While researchers have only begun to discuss the changing landscape of marketing and consumer behavioral research in this era (e.g., Mehta et al, 2022; Paul et al, 2023), the use of AI chatbots likely will transform how consumers, providers, and platforms make decisions. Furthermore, prosumers sentiments' regarding their own vulnerability and the risks associated with sharing economy participation possibly will be affected as well.…”
Section: Discussionmentioning
confidence: 99%
“…Most CE publications leverage consumers' interactive experiences on digital platforms, for example, social media platforms and virtual brand communities, to obtain data for their research (Barari et al, 2021; Brodie et al, 2013; Saikia & Bhattacharjee, 2023). These investigations have demonstrated that consumers tend to direct their resources in online interactions, like interacting with peers and participating in discussions on a web site or ChatGPT platform (Calder et al, 2009; Paul et al, 2023), and develop brand‐related sense‐making (Hollebeek & Macky, 2019), resulting in buying behavior, customer referral behavior, customer‐to‐customer interactions, word‐of‐mouth activity, and/or blogging activity, brand love, and other consumer‐based brand equity (Arya et al, 2022; Joshi & Garg, 2021; Kumar et al, 2010; Van Doorn et al, 2010). Other scholars (e.g., Baldus et al, 2015; Raïes et al, 2015) pointed out that consumers develop CE by participating in online brand‐related activities and discussions and forming a brand community to conduct activities such as seeking assistance, like‐minded discussion, and self‐expression.…”
Section: Literature Review and Theoretical Hypothesismentioning
confidence: 99%